Not all babies are in the same boat: Exploring the effects of socioeconomic status, parental attitudes, and activities during the 2020 COVID‐19 pandemic on early Executive Functions. (31st January 2022) - Hendry, Alexandra; Gibson, Shannon P.; Davies, Catherine; Gliga, Teodora; McGillion, Michelle; Gonzalez‐Gomez, Nayeli
Abstract: Early executive functions (EFs) lay the foundations for academic and social outcomes. In this parent‐report study of 575 UK‐based 8‐ to 36 month olds (218 followed longitudinally), we investigate how variation in the home environment before and during the 2020 pandemic relates to infants' emerging EFs. Parent‐infant enriching activities were positively associated with infant Cognitive Executive Function (CEF) (encompassing inhibitory control, working memory, cognitive flexibility). During the most‐restrictive UK lockdown—but not subsequently—socioeconomic status (SES) was positively associated with levels of parent‐infant enriching activities. Parents who regard fostering early learning, affection, and attachment as important were more likely to engage in parent‐infant enriching activities, yet there was no significant pathway from parental attitudes or SES to CEF via activities. Infant screen use was negatively associated with CEF and Regulation. Screen use fully mediated the effect of SES on CEF, and partially mediated the effect of SES on regulation. Parental attitudes toward early learning, affection, and attachment did not significantly influence screen use. These results indicate that although parental attitudes influence the development of early EFs, interventions targeting attitudes as a means of increasing enriching activities, and thus EF are likely to be less effective than reducing barriers to engaging in enriching activities.